1982
DOI: 10.1007/bf00333788
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of SOS functions and modulation of mutagenesis resulting from resolution of genetic instability at or near the recA locus of Escherichia coli

Abstract: Cellular activities normally inducible by DNA damage (SOS functions) are expressed, without DNA damage, in recA441 (formerly tif-1) mutants of Escherichia coli at 42 degrees C but not at 30 degrees C. We describe a strain (SC30) that expresses SOS functions (including mutator activity, prophage induction and copious synthesis of recA protein) constitutively at both temperatures. SC30 is one of four stable subclones (SC strains) derived from an unstable recombinant obtained in a conjugation between a recA441 K1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
72
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(76 citation statements)
references
References 39 publications
4
72
0
Order By: Relevance
“…The RecA protein encoded by recA 718 causes moderate UV sensitivity but is competent in recombination, in SOS induction, and in all known RecAmediated proteolytic activities (10,17). We found that recA 718 polAI mutants were conditionally inviable.…”
mentioning
confidence: 74%
“…The RecA protein encoded by recA 718 causes moderate UV sensitivity but is competent in recombination, in SOS induction, and in all known RecAmediated proteolytic activities (10,17). We found that recA 718 polAI mutants were conditionally inviable.…”
mentioning
confidence: 74%
“…We also investigated the orientation bias for the SOS mutator effect, as mediated by the constitutive recA730 allele. In recA730 strains, the SOS system is induced constitutively, leading to increased mutagenesis in the absence of DNA-damaging treatments (untargeted mutagenesis) (10,39,40). We found, interestingly, that the orientation bias is inversed under these conditions and that, apparently, lagging strand replication is the major source of the mutations (22).…”
mentioning
confidence: 75%
“…This increased mutagenesis has been called the "SOS mutator activity" or "untargeted mutagenesis" (39,40). Like targeted mutagenesis, the SOS mutator activity depends on the umuDC genes (5).…”
mentioning
confidence: 99%
“…Bacterial Strains and Media-The strain used for isolating AZTresistant mutants is known as SC18-12 and has the genotype recA718 polA12 uvrA155 trpE65 lon-11 sul A1 (11). The strain BL21 DE3 was used for protein expression and has genotype FϪ ompT hsdSB(rBmBϪ) gal dcm (DE3).…”
Section: Methodsmentioning
confidence: 99%